Detection and classification of falling in elderly people using customized deep learning algorithm (Sulaimani Journal for Pure and Applied Sciences, 2021)
This research work proposes a fall detection system in elderly people based on customized human body detection using You Only Look Once (YOLO) version-3 algorithm. This scheme provides a high accuracy rate of classification for different cases (stand, sit, and fall). To design such system, IoT based-fall detection is implemented. The Raspberry pi is used to process the tested images captured from the live camera. Then, the YOLO detects the human body and classifies them into three categories. The proposed system has trained for 100 images for each class type based on positive samples. Moreover, in the test phase, static image, and live camera have been used to show the performance of the system in term of the accuracy detection. Finally, the accuracy rate is determined for different distances from the camera in order to improve the validity of the classification. Test results indicate that the proposed system is invariant for the light and environmental conditions and has a good accuracy when the live camera is used. The accuracy rates average of a live camera for different distances are 100%, 95%, and 90% for (stand, sit, and fall) classes respectively.
Keywords: Biometric; Fall detection; Fall classification Customized deep learning; Accuracy detection